Los monos = Monkeys - Macken, JoAnn Early, 1953- (Milwaukee, WI : Weekly Reader Early Learning, 2005)
Provides a brief description of a variety of monkeys you might see at the zoo.
Includes bibliographical references (p. 23) and index.
Keywords: Monkeys -- Juvenile literature; Zoo animals -- Juvenile literature; Monkeys; Zoo animals; Spanish language materials -- Bilingual; Monos -- Literatura juvenil; Animales zoologicos -- Literatura juvenil